Advances in the translational genomics of neuroblastoma: From improving risk stratification and revealing novel biology to identifying actionable genomic alterations - Bosse, Kristopher R.; Maris, John M. (Cancer, 2016)
Neuroblastoma is an embryonal malignancy that commonly affects young children and is remarkably heterogenous in its malignant potential. Recently, the genetic basis of neuroblastoma has come into focus and not only has catalyzed a more comprehensive understanding of neuroblastoma tumorigenesis but also has revealed novel oncogenic vulnerabilities that are being therapeutically leveraged. Neuroblastoma is a model pediatric solid tumor in its use of recurrent genomic alterations, such as high‐level MYCN (v‐myc avian myelocytomatosis viral oncogene neuroblastoma‐derived homolog) amplification, for risk stratification. Given the relative paucity of recurrent, activating, somatic point mutations or gene fusions in primary neuroblastoma tumors studied at initial diagnosis, innovative treatment approaches beyond small molecules targeting mutated or dysregulated kinases will be required moving forward to achieve noticeable improvements in overall patient survival. However, the clonally acquired, oncogenic aberrations in relapsed neuroblastomas are currently being defined and may offer an opportunity to improve patient outcomes with molecularly targeted therapy directed toward aberrantly regulated pathways in relapsed disease. This review summarizes the current state of knowledge about neuroblastoma genetics and genomics, highlighting the improved prognostication and potential therapeutic opportunities that have arisen from recent advances in understanding germline predisposition, recurrent segmental chromosomal alterations, somatic point mutations and translocations, and clonal evolution in relapsed neuroblastoma. Cancer 2016;122:20–33. © 2015 American Cancer Society. Advances in defining the biologic importance of neuroblastoma‐associated genomic aberrations and the genetic underpinnings of neuroblastoma predisposition have led not only to improved risk stratification but also to novel insights into activated oncogenic pathways and to the first molecularly targeted agent for this disease. Defining the clonally evolved neuroblastoma genome may unveil additional activated and clinically actionable biologic pathways.